Shape completion with a 3D Convolutional Neural Network for multi-domain O&M activities in offshore wind farms. - Ricardo Fernando de Freitas Dinis (2020)
An autonomous vehicle needs to understand its surrounding environment to plan routes and avoid collisions. For that purpose, they are equipped with appropriate sensors which allow them to capture the necessary information. The maritime environment presents additional which make it hard to have a clear picture of the nearby structures. In this work, the goal is to use the available sensor information to infer the complete shape of nearby structures. The approach is divided into three main components: clustering, classification, and registration. The clustering is used to detect sizeable structures and remove irrelevant ones. The resulting data is voxelized, and classified, by a 3D CNN, as one of the studied structures. Finally, a hybrid PSO-ICP registration method is used to fit a complete CAD model on the observed data.